A herança de Dioniso: uma visão junguiana sobre filhas e filhos adultos com pai alcoolista - Chaves, Pedro (2023)
This research is a qualitative study about adults who have or had an alcoholic father. For that, a semi-structured interview was carried out with four women and four men, and a discussion of the results theoretically based on analytical psychology. Despite the vast scientific literature, studies that deepen the influence of gender in the construction of these subjects' identity and their adaptive roles within the family and society are still embryonic. Contemporary studies come up against data that point to the importance of problematizing this issue (for example, when they attest to a greater occurrence of a behavioral inhbition in these daughters, and greater aggressiveness in these sons), although some conclusions in the literature are repeated without being significantly updated since the 1990s: male children continue to be illustrated as impulsive and prone to reproducing their father's alcoholism, and female daughters as more inhibited and codependent, looking for their father in a husband. However, the results of this research suggest that there is an ongoing transformation: the contemporary changes in the roles assigned to the genders, as well as the crises to which these daughters and sons tend to be exposed, seem to reconfigure those attitudes recognized as typical of each gender. Therefore, the current scenario illustrates greater complexity: for example, women who are also capable of aggressively defending themselves and men who are also structured in a codependent way. Even from the tragic backdrop of these families, once stable meanings about gender seem open to innovations. In this way, the Jungian and post-Jungian perspective based the analysis of the people interviewed and the central themes of this research – fatherhood, alcoholism and gender – in light of the symbolic meanings woven from the destinies and possible exits for these subjects